Limitation in The Right to Freedom of Thought, Conscience, and Religion (Forum Externum): Study of Ahmadiyya Muslim Community Case - Mega Jaya, Belardo Prasetya; Nurikah, Nurikah; Prasetya, Ahadi Fajrin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: According to General Explanation of Presidential Decree No. 1/PNPS/ 1965 on Prevention of Misuse and/or Blasphemy, there are six religions in Indonesia. There are Islam, Kristen, Katolik, Hindu, Budha, and Khong Cu (Confucius). It raises the issue of Indonesian who choose conscience or religions out of the six religions. One example is the Ahmadiyya Muslim Community who choose their conscience. Ahmadiyya Muslim Community often received public rejection and some limitations from the Government of Indonesia.  This paper aims to: (1) examine and analyze the international instrument about the limitation in the right to freedom of thought, conscience, and religion (Forum externum); (2) observe and value the limitation in the right to freedom of thought, conscience, and religion (Forum externum) in Indonesia (Ahmadiyya Muslim Community case). Deploying normative legal research, this research argues that the limitations in religious activities and sealing of several places of worship of the Ahmadiyya Muslim Community by the Government have a legal basis in the international law of externum forum principle and that- the Government limitation on religious activities of Ahmadiyya Muslim community is designed and applied to protect public safety, order, health, or morals or the fundamental rights and freedoms of others. Abstrak: Berdasarkan Penjelasan Umum Penetapan Presiden Republik Indonesia No. 1/PNPS/1965 tentang Pencegahan Penyalahgunaan dan/atau Penodaan Agama. Hanya Ada 6 agama di Indonesia yaitu Islam, Kristen, Katolik, Hindu, Budha dan Khonghucu (Confusius). Pembatasan enam agama tersebut menimbulkan persoalan mengenai bagaimana warga negara Indonesia yang memilih kepercayaan atau agama selain dari ke enam agama tersebut, seperti kelompok Muslim Ahmadiyya yang memiih kepercyaannya sendiri. Kelompok Muslim Ahmadiyya sering mendapatkan penolakan publik dan pembatasan-pembatasan dari Pemerintah Indonesia. Penelitian ini bertujuan untuk: (1) menguji dan menganalisis instrumen internasional mengenai pembatasan hak untuk berfikir, berkeyakinan dan beragama (forum eksternum); dan (2) mengamati dan menilai bagaimana implementasi hak untuk berfikir, berkeyakinan dan beragama (forum eksternum) di Indonesia (kasus Kelompok Muslim Ahmadiyya). Dengan pendekatan hukum normatif, penelitian ini membuktikan bahwa pembatasan-pembatasan dalam melakukan kegiatan keagamaan dan penyegelan beberapa tempat ibadah jemaah Ahmadiyya oleh Pemerintah memiliki basis hukum dalam hukum internasional yakni prisip forum eksternum dan pembatasan pemerintah terhadap kelompok Muslim Ahmadiyya diterapkan demi tercipta keselamatan, ketertiban, kesehatan, atau kesusilaan umum, atau hak-hak dan kebebasan-kebebasan mendasar milik orang lain.